Empowering women and advancing peace: A study of wahid foundation’s initiatives for inclusive social transformation in Indonesia - Siswoyo Aris Munandar; Mohammad Mu'tashim Billah (An-Nisa’ Journal of Gender Studies, 2025)
The increasing spread of radicalism in rural areas places women as the most affected group; however, they remain excluded from peacebuilding and development processes. This situation reflects a serious irony that may threaten the long-term social sustainability of Indonesia’s future. This study analyzes the Peace Village Program’s response to rural radicalism through women’s empowerment and evaluates its impact on peace declarations and cooperative-based economic institutions. This qualitative case study employed document analysis, participatory observation, and interviews. Data were analyzed thematically using source triangulation and audit trail techniques to ensure validity and adherence to research ethics. The study findings indicate that: (1) the Peace Village Program responds to rural radicalism by empowering women through strengthening tolerance, peace, economic capacity, as well as training and advocacy; (2) the program successfully declares peace villages and empowers women as entrepreneurs; and (3) economic empowerment through the Peace Village Cooperative integrates nine peace indicators, establishes Village-Owned Enterprises (BUMDes), and distributes loans. The study concludes that the Peace Village Program effectively addresses radicalism and empowers women economically, but high participation does not ensure substantive power due to elite dominance and donor dependency. This study contributes to strengthening an integrative approach to village-based peacebuilding and emphasizes the importance of a power perspective, while highlighting the need to enhance women’s capacity, local institutions, and economic sustainability.